2021
DOI: 10.1101/2021.03.15.435481
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of the PcrA-RNA polymerase complex reveals a helicase interaction motif and a role for PcrA/UvrD helicase in the suppression of R-loops

Abstract: The PcrA/UvrD helicase binds directly to RNA polymerase (RNAP) but the structural basis for this interaction and its functional significance have remained unclear. In this work we used biochemical assays and hydrogen-deuterium exchange coupled to mass spectrometry to study the PcrA-RNAP complex. We find that PcrA binds tightly to a transcription elongation complex in a manner dependent on protein:protein interaction with the conserved PcrA C-terminal Tudor domain. The helicase binds predominantly to two positi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…subtilis RNaseJ1 clears stalled RNAP using a torpedo mechanism (5′–3′ exonuclease activity followed by RNAP displacement) (Sikova et al, 2020), and in Escherichia coli the helicase protein RapA is important in recycling RNAP (Liu et al, 2015). UvrD/PcrA in concert with Gre factors has been reported to act on RNAP stalled at a DNA lesion, binding to the complex and using the energy of ATP hydrolysis to backtrack away from the lesion to allow repair systems access to the damaged DNA (Epshtein et al, 2014; Hawkins et al, 2019), although it now appears that the role of these helicases is in preventing the formation of, and resolving, R‐loops (RNA‐DNA hybrids) that can have a detrimental effect on DNA replication (Urrutia‐Irazabal et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…subtilis RNaseJ1 clears stalled RNAP using a torpedo mechanism (5′–3′ exonuclease activity followed by RNAP displacement) (Sikova et al, 2020), and in Escherichia coli the helicase protein RapA is important in recycling RNAP (Liu et al, 2015). UvrD/PcrA in concert with Gre factors has been reported to act on RNAP stalled at a DNA lesion, binding to the complex and using the energy of ATP hydrolysis to backtrack away from the lesion to allow repair systems access to the damaged DNA (Epshtein et al, 2014; Hawkins et al, 2019), although it now appears that the role of these helicases is in preventing the formation of, and resolving, R‐loops (RNA‐DNA hybrids) that can have a detrimental effect on DNA replication (Urrutia‐Irazabal et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In B. subtilis RNaseJ1 clears stalled RNAP using a torpedo mechanism (5'-3' exonuclease activity followed by RNAP displacement) (Sikova et al, 2020), and in Escherichia coli the helicase protein RapA has been shown to be important in recycling RNAP (Liu et al, 2015). UvrD/PcrA in concert with Gre factors has been reported to act on RNAP stalled at a DNA lesion, binding to the complex and using the energy of ATP hydrolysis to backtrack away from the lesion to allow repair systems access to the damaged DNA (Epshtein et al, 2014, Hawkins et al, 2019, although it now appears that the role of these helicases is in preventing formation of, and resolving, R-loops (RNA-DNA hybrids) that can have a detrimental effect on DNA replication (Urrutia-Irazabal et al, 2021).…”
Section: Introductionmentioning
confidence: 99%